Epistemology new essays - Smith, Quentin, 1952- (Oxford : Oxford University Press, 2008)
This volume offers a view of the state of play in epistemology in the form of 12 new essays by some of the most influential epistemologists of recent years. Topics include epistemic justification, solipsism, skepticism, reliabilism evidentialism, infinitism, and modal, moral, naturalistic, and probabilistic epistemology.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Knowledge, Theory of